E-Learning and Change in Higher Education: The Policy Environment - A. Mee (University of Sofia, 2007)
This paper critically examines the role of government policy with respect to e-learning as an agent of change in the higher education sector. The potential impact of e-learning on the structure and organisation of the higher education sector has become a central issue for managers at institutional level and government policy makers across the globe. There is clear evidence from a range of policy documents from various nations of a general acceptance that an imperative exists to engage with the 'knowledge economy' in order to secure or retain a competitive economic advantage in the global order. It is seen that emerging digital technologies have a central role to play in this task and many governments have been active in promoting the development of e-learning as an agent of improvement, capacity building and organisational change in the higher education sector. Evidence is available that such technologies, supported by government policy, have served to enhance the quality of the student experience within the existing organisational and pedagogical frameworks which characterise the majority of higher education institutions. There is, however, little evidence of radical restructuring or the 'transformation' of existing institutions into the 'virtual universities' envisioned by some early commentators. This paper explores the wider policy context within which governments must work if they are to reap the full benefits of emerging technologies.